Education management in the new normal era: a literature study - Hanum, Gilang Kartika; Prayitno, Hadi; Mubarok, Ahmad; Pasongli, Hernita; Mendrofa, Netti Kariani (Academy of Education Journal, 2024)
The objective of this article is to offer a general overview of how face-to-face learning can be utilized in the context of the new normal era and to identify potential learning models that teachers can employ in addressing educational challenges within this era. In the process of developing this article, a literature review method was employed. The data collection process included a comprehensive review of various references from national and international journals that are pertinent to the subject matter under discussion. Upon conducting thorough research, the author will then select, analyze, and present results in a systematic manner. The learning model represents a significant element within the context of learning. As an individual occupying a pivotal role in the learning process, the teacher is responsible for applying an optimal learning model to ensure the successful attainment of learning objectives. A selection of models that can be utilized for learning within the new normal era includes: Three learning models are worthy of mention: Blended Learning, Flipped Classroom, and Hybrid Learning. In applying any of the aforementioned models to the learning process, it is important to consider the specific characteristics of each learner and the abilities of the instructor.